2018
DOI: 10.1016/j.ces.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A critical review on the use of nanoparticles in liquid–liquid extraction

Abstract: Recently, the use of nanoparticles in extraction columns has gained increasing attention due to their potential to enhance mass transfer processes. Most of the reported work, however, has been concerned with mass transfer enhancement in gas-liquid systems in the presence of nanoparticles, while limited studies of liquid-liquid systems have been reported. Liquidliquid extraction is an extensively employed separation method that has taken on a substantial role in engineering and industrial applications for recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 166 publications
0
5
0
Order By: Relevance
“…Nanofluids have attracted great attention as effective working fluids in heat and mass transfer enhancement. It is found that the addition of a small amount of nanoparticles exert considerable impact on the hydrodynamic and mass transfer performance of solvent extraction processes [161,162]. Although it has a prosperous future in process intensification, limited attempts are made in liquid-liquid extraction.…”
Section: Nanofluid Intensification Of Extractionmentioning
confidence: 99%
“…Nanofluids have attracted great attention as effective working fluids in heat and mass transfer enhancement. It is found that the addition of a small amount of nanoparticles exert considerable impact on the hydrodynamic and mass transfer performance of solvent extraction processes [161,162]. Although it has a prosperous future in process intensification, limited attempts are made in liquid-liquid extraction.…”
Section: Nanofluid Intensification Of Extractionmentioning
confidence: 99%
“…The use of a nanoparticle-embedded system could enhance the overall extraction efficiency of the process due to perturbation and micromixing around the embedded nanoparticles. , Nickel nanoparticles are used in the current work because of their superior ferromagnetic and surface properties (high coercive forces, chemical stability, and magnetocrystalline anisotropy). Nanoparticles can be easily embedded within glass millichannels using an aminosilane method. , Other metal oxide nanoparticles can also potentially improve mass transfer, but permanent immobilization of the nanoparticles is not achievable because these nanoparticles will rapidly leach out in the absence of chainlike structures.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that conventional fluids could be substituted with nanofluids for the aim of process intensification. A detailed review on utilizing nanofluids in various columns with different chemical systems has been presented by Amani et al 3 The main liable mechanism of the enhancing effect of nanofluids is related to the Brownian motion, random movement of nanoparticles, and subsequent internal convection. Small nanoparticles with lower density are more capable for this aim 1 .…”
Section: Introductionmentioning
confidence: 99%